Regulation of Rubisco Carboxylation Activity and Photosynthetic Rate by Rubisco Activase during Leaf Senescence in Rice - JIANG De-an; LU Qing; WENG Xiao-yan; ZHEN Bing-song; XI Hai-fu (浙江大学学报. 农业与生命科学版)
Photosynthetic rate, contents of soluble protein, chlorophyll, Rubisco and Rubisco activase, activities of Rubisco initial carboxylation and Rubisco activase were traced to clarify whether Rubisco activase regulates Rubisco activity and photosynthetic rate during flag leaf senescence. There were highly positive correlation between Rubisco activase activity and Rubisco initial carboxylation activity (r2=0.810 3), and between Rubisco activase activity and photosynthetic rate (r2=0.702), between Rubisco activase content and Rubisco activase activity (r2=0.814 3) as well as between Rubisco initial carboxylation activity and photosynthetic rate (r2=0.966 3). The ratio of Rubisco activase to Rubisco content (0.5%-1.0%) or soluble protein content (0.5%-0.6%) was higher in young leaf than in old leaf. It can be suggested that Rubisco activase play an important role in controlling Rubisco initial activity and Pn in process of leaf senescence in rice plant.